Western Europe and the new international economic order : representative samples of European perspectives - Laszlo, Ervin, 1932-; Kurtzman, Joel (Pergamon policy studies on the new international economic order., 1980)
Western Europe and the New International Economic Order examines the views and positions of Western European nations regarding the New International Economic Order (NIEO). The factors influencing such positions are analyzed, namely, economic factors on the one hand, and social, political, and cultural factors on the other.